The Outer Membrane of Brucella ovis Shows Increased Permeability to Hydrophobic Probes and Is More Susceptible to Cationic Peptides than Are the Outer Membranes of Mutant Rough Brucella abortus Strains - Freer, Enrique (American Society for Microbiology, 1999)
The permeability of the outer membrane (OM) to hydrophobic probes and its susceptibility to bactericidal cationic peptides were investigated for natural rough Brucella ovis and for mutant rough Brucella abortus strains. The OM of B. ovis displayed an abrupt and faster kinetic profile than rough B. abortus during the uptake of the hydrophobic probe N-phenyl-naphthylamine. B. ovis was more sensitive than rough B. abortus to the action of cationic peptides. Bactenecins 5 and 7 induced morphological alterations on the OMs of both rough Brucella strains. B. ovis lipopolysaccharide (LPS) captured considerably more polymyxin B than LPSs from both rough and smooth B. abortus strains. Polymyxin B, poly-l-lysine, and poly-l-ornithine produced a thick coating on the surfaces of both strains, which was more evident in B. ovis than in rough B. abortus. The distinct functional properties of the OMs of these two rough strains correlate with some structural differences of their OMs and with their different biological behaviors in animals and culture cells.